2013
DOI: 10.1007/s11414-012-9314-y
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Treatment Patterns and Aggressive Behavior Among Adolescents in Residential Facilities

Abstract: This study examined the association between acute aggressive behavior patterns of 145 adolescents in residential treatment facilities with use of and changes in antipsychotic medication for the chronic management of aggression. Seclusion/restraint (S/R) frequency over 12 months was used to categorize youth into none, low, moderate, and high S/R groups. Data were analyzed using longitudinal mixed effects logistic regression models that allowed for intra-subject variability over time. The high and moderate S/R g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…In our study, we find that risperidone is the commonly prescribed antipsychotic. Now a days most patient's presents with coexisting depressive symptoms and hence antidepressants are also added to prescriptions which correlate with the use of escitalopram in our study findings [24]. The other group of drugs that are co-prescribed are the benzodiazepines (diazepam and clonazepam), anticholinergic (Trihexyphenidyl), carbamazepine and antidepressants (escitalopram) contributing to 43.47%, 26.08%, 21.74% and 13.04% respectively…”
Section: Observed Drug Use Pattern In Pddsupporting
confidence: 55%
“…In our study, we find that risperidone is the commonly prescribed antipsychotic. Now a days most patient's presents with coexisting depressive symptoms and hence antidepressants are also added to prescriptions which correlate with the use of escitalopram in our study findings [24]. The other group of drugs that are co-prescribed are the benzodiazepines (diazepam and clonazepam), anticholinergic (Trihexyphenidyl), carbamazepine and antidepressants (escitalopram) contributing to 43.47%, 26.08%, 21.74% and 13.04% respectively…”
Section: Observed Drug Use Pattern In Pddsupporting
confidence: 55%
“…A study of adolescents in two US residential treatment centers found that adolescents with moderate and high levels of seclusion and restraint were more often black and/or female [30, 31]. However, there are studies of adolescents with different findings that give a more inconclusive picture of the evidence [17, 18, 21, 32].…”
Section: Discussionmentioning
confidence: 99%
“…The use of chemical restraints are still controversial and there is little information on their prevalence and effectiveness in children in the literature at this time (Crocker, Stargatt, & Denton, 2010;Dean, McDermott, & Marshall, 2006;Vitiello et al, 1991). A recent study by Miller, Riddle, Pruitt and Zachik (2013), led the researchers to question the effectiveness of medication in managing aggressive behavior when higher doses of antipsychotic medications did not decrease the prevalence of seclusion and physical restraint practices in an adolescent residential treatment facility. Due to the limited knowledge on the use of psychotropic medications in children, many recommend prescribing them cautiously and ensuring a psychosocial component to treatment as well (Connor & Meltzer, 2006;Olfson, Marcus, Weissman, & Jensen, 2002).…”
Section: An Overview Of Restraints and Seclusionmentioning
confidence: 99%
“…Factors such as younger age (Donovan, Plant, Peller, Siegel, & Martin, 2003;Duke et al, 2014;Pogge et al, 2013;Stewart, Baiden, & Theall-Honey, 2013), increased risk for aggression (Duke et al, 2014;Sourander et al, 2002), psychotic symptoms (Sourander, Ellilä, Välimäki, & Piha, 2002;Delaney & Fogg, 2005;Ulla, Maritta, & Rittakerttu, 2012), longer length of stay (Stewart et al, 2013;Sourander et al, 2002;Delaney & Fogg, 2005;Furre et al, 2014), and involuntary admission increased the likelihood that an individual would experience a restraint or seclusion Furre et al, 2014). Additionally, residents who were female, black, diagnosed with an anxiety/mood disorder, or receiving antipsychotic/mood stabilizers were more likely to be restrained or secluded (dosReis et al, 2010;Miller et al, 2013;Azeem, Aujlia, Rammerth, Binsfeld, & Jones, 2011). Delaney and Fogg (2005) found that patients were significantly more likely to be restrained if they were male, had been admitted multiple times to the facility, remained in the hospital longer, had been given a diagnosis of a psychotic disorder, or had a previous psychiatric hospitalization.…”
Section: An Overview Of Restraints and Seclusionmentioning
confidence: 99%